Mille-feuille shaped hard carbons derived from polyvinylpyrrolidone via environmentally friendly electrostatic spinning for sodium ion battery anodes. Issue 9 (17th January 2017) - Bai, Ying; Liu, Yuanchang; Li, Yu; Ling, Liming; Wu, Feng; Wu, Chuan
Abstract : Mille-feuille shaped hard carbons derived from polyvinylpyrrolidone (PVP) nanofibrous via simple electrostatic spinning achieve excellent electrochemical performances as anode materials for sodium ion batteries. Abstract : Pursuing low-cost and high-performance anode materials is of great importance for developing practical sodium ion batteries. In this work, mille-feuille shaped hard carbons derived from low-cost and environmentally friendly polyvinylpyrrolidone (PVP) nanofibres are fabricated via simple electrostatic spinning and followed by further pyrolysis at 800–1200 °C, as anode materials for sodium ion batteries. The optimized sample HC-1000 carbonized at 1000 °C shows better particle size and low surface area, and achieves a good reversible capacity of 271 mA h g −1 with 94% capacity retention ratio over 100 cycles. In addition, HC-1000 exhibits satisfactory rate performance, namely, the discharge capacities are 304, 264, 209, 142, 109 and 70 mA h g −1 at a current density of 20, 40, 100, 200, 500 and 1000 mA g −1 after 10 cycles respectively. Even continuing with an additional 280 cycles at 200 mA g −1, the capacity retains 285 mA h g −1 when the current recovers to 20 mA g −1 . The mille-feuille shaped morphology, uniform particle size distribution and low surface area enable excellent electrochemical performances of PVP based hard carbon, which is expected to be a promising anode material for Na-ion batteries.